Rapid surface preparation for three-dimensional characterization of defect and microstructure of metal additive manufacturing using electrochemical jet. (15th December 2021) - Lu, Jiajun; Liu, Weidong; Hu, Xiaogang; Wang, Shuai; Tang, Guoping; Zhao, Yonghua
Graphical abstract: Highlights: EJSP for versatile characterization of additively manufactured metal is proposed. EJSP can achieve both bulk removal and surface generation with the varying current. EJSP provides both microstructure-defined and polished surface topography. EJSP spatially reveals defects and microstructures of SLM parts at multiscale. EJSP enables three-dimensional reconstruction of the SLM microstructure by slicing. Abstract: Process-induced volume defects and unsuitable microstructure have inhibited the effective quality assurance of parts manufactured by selective laser melting (SLM). Elucidating the complex interaction between the process, defect/microstructure, and performance is of critical importance. In this work, we have developed and demonstrated the capabilities of an electrochemical jet surface processing (EJSP) method to easily and effectively uncover defects and unveil the crystal microstructure and fusion mechanism in SLM parts of SUS316L and AlSi10Mg respectively. Experiments show that the EJSP method is highly effective in localized three-dimensional microstructural unveiling which eliminates the need for conventional sample preparation by polishing, and internal defects and retained fusion signatures at multiple layers are readily identified within seconds. Furthermore, EJSP unveils three-dimensional structural information at both micro- and nano-scale to facilitate crystallography and phase analysis. This unique approach has high potential to significantly improve qualification methods of SLM parts, which benefits in-depth research of microstructure characteristics and their formation mechanism in the SLM process with high efficiency and low cost.